Use of prostaglandin E-1 in obstetrics. - Cáceres, Eduardo (2015)
OBJECTIVE: Study of prostaglandin E-1 in uterine evacuation, as an alternative to oxitocin and hysterotomy. MATERIAL: 176 patients treated with prostaglandin E-1 for uterine evacuation, performed at the Obstetrics Departament of Edgardo Rebagliati Martins National Hospital, Social Security Peruvian Institute. METHOD: Combined vaginal and oral administration of prostaglandin E-1.  RESULTS: Success was obtained lu 168 cases (95,5%) and failure in 8 (4.5%). Secondary effects were minimal, hospital stay was shorter and complementary treatments were facilitated. CONCLUSIONS: Low percentage of failures and rare presentation of secondary effects make this product indispensable in our specialty.